Waste Heat Recovery from Air Using Porous Media and Conversion to Electricity - Henriquez-Vargas, L; Donoso-Garcia, P (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
This paper presents a numerical study of waste heat recovery from a fluid stream using thermoelectric devices. The system consisted of a square section duct with spherical porous media placed in its central region. Hot air circulates continuously through the duct and exchanges energy with the solid matrix and subsequently with the thermoelectric modules. The mathematical model of the system was solved using ANSYS/FLUENT software, requiring the implementation of user-defined functions (UDFs) and user-defined scalars (UDS) regarding porous media and thermoelectric generation modelling. From the simulations carried out, global efficiency and electrical power values were obtained in the range of [0.11–4.51] [%] and [0.01–12.77] [W], respectively. Furthermore, for the set of variables analysed, it was observed that the performance of the system is favoured by an increase in the fluid inlet temperature and speed, as well as by a higher external heat transfer coefficient. © 2022 by the authors.